Diclofenac in vitro microdialysis study comparing different experimental set‐ups to improve quantitative recovery. Issue 4 (2nd February 2022) - Jorda, Anselm; Armogida, Marianna; Lackner, Edith; Saikumar, Sivasankari; Sucharski, Filip; Weber, Maria; Zeitlinger, Markus
Abstract: Several studies investigated diclofenac tissue concentrations using microdialysis (MD). However, thorough evaluations of the optimal MD set‐up for diclofenac are unavailable. Thus, this in vitro MD study aimed to compare different set‐ups to improve quantitative recovery of diclofenac. In forward and reverse in vitro MD experiments with diclofenac at two concentrations (1 and 100 ng/ml), the perfusion solutions physiological saline 0.9% (PS) and human albumin 1% (HSA) were compared using tissue probes (10‐mm membrane) and customized intravenous (iv) probes (30‐mm membrane). Using PS, the mean relative recovery of diclofenac at 1 ng/ml was 1.6% ± 0.04% and 3.12% ± 0.00% with the tissue probe and the iv probe, respectively. The respective mean relative recovery for diclofenac at 100 ng/ml was 0.02% ± 0.01% and 0.21% ± 0.11%. Using HSA, the mean relative recovery was 314% ± 25% (tissue probe) and 1064% ± 97% (iv probe) for diclofenac at 1 ng/ml and 444% ± 91% and 1415% ± 217% for diclofenac at 100 ng/ml. In reverse dialysis using PS, the mean relative loss of diclofenac was 99.2% ± 0.5% (tissue probe) and 95.8% ± 1.7% (iv probe). Using HSA, the mean relative loss was −4.4% ± 7.2% and 0.2% ± 7.5%, respectively. PS and HSA were not suitable perfusion solutions for quantification of absolute diclofenac concentrations. Despite methodological challenges, HSA may be used for comparative experiments or bioequivalence studies.